Design of a Study to Measure Patient-Perspectives in Adverse Event Reporting (the PPAR Study): Supplementary Study to the ASPIRe Trial. Issue 1 (January 2021) - Sung, Vivian W.; Menefee, Shawn; Dunivan, Gena; Richter, Holly E.; Moalli, Pamela; Weidner, Alison; Andy, Uduak Umoh; Jelovsek, Eric; Mazloomdoost, Donna; Whitworth, Ryan; Thomas, Sonia
Abstract : Objectives: The primary objective of this study is to compare patient versus physician rankings of adverse event (AE) and adverse symptom (AS) severity after pelvic reconstructive surgery. Secondary objectives include to estimate the association between patient rankings of AEs/ASs with decision-making and quality-of-life outcomes and to determine whether patient perspective about AE/AS changes over time. Methods: This is a supplementary study, Patient-Perspectives in Adverse Event Reporting (PPAR), to the index trial, ASPIRe (Apical Suspension Repair for Vault Prolapse In a Three-Arm Randomized Trial Design). During the trial, AEs/ASs will be assessed by physicians longitudinally every 6 months, which includes a determination of the AE/AS grade severity. For PPAR, additional patient perspective will be measured for 19 predetermined AEs/ASs at the time of identification and again at 12 and 36 months postoperatively. Decision-making and quality-of-life questionnaires will be collected at these time points. The primary outcome, the overall interrater agreement between patient and physician rankings for AE/AS severity, will be determined using a repeated-measures concordance correlation coefficient. Results: To date, the index trial has completed enrollment, and follow-up is ongoing. Conclusions: The PPAR methods for incorporating patient perspective in the measurement of AEs/ASs to determine their agreement with physician ranking, long-term relevance, and impact on treatment decision making and quality of life are described. This will contribute to improved measurements of AEs/ASs in future research with the goal of improving patient counseling and informing expectations and treatment decision making.